ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA ROTI BAKAR BANDUNG BONDOWOSO (Studi Kasus Pada Franchise RB. Duzzi) - Syama, Nur Izzuddien; Rachman, Riza; Anhar, Muh. Barry Nur; Safitri, Fina; Rahman, Yasyfi Aufa; As’adiyah, Bunga Banafsaj Amiratul (Fakultas Ekonomi dan Bisnis, 2022)
This research intend to analyze marketing strategies that can increase sales at Roti Bakar Bandung Bondowoso (RB. Duzzi), a toast franchise. In the context of increasingly fierce competition, effective marketing strategies are the key to success in increasing sales. Through a SWOT analysis approach (Strengths, Weaknesses, Opportunities and Threats), this research explores the internal and external factors that influence RB sales. Duzzi. The results of this research provide a better understanding of the strengths, weaknesses, opportunities and threats faced by RB. Duzzi, as well as providing recommendations for marketing strategies that can be implemented to increase sales. Thus, this research contributes to the development of more effective marketing strategies in the context of the toast franchise business.